Pollution characteristics and risk assessment of heavy metals in the water and surface sediments of Wulungu Lake, Xinjiang China. Issue 1 (2nd January 2023) - Liu, Fengyu; He, Shaohua; Tong, Yanbin; Wang, Manli; Li, Min; Lu, Jianjiang
ABSTRACT: Wulungu Lake is the second largest lake and the second largest fishery base in Xinjiang, but there are few studies on heavy metal pollution in water environment. In order to explore the characteristics and sources of heavy metal pollution in the water environment of Wulungu Lake, the distribution characteristics, ecological risks and pollution sources of 8 heavy metals (Cr, Cu, Cd, Zn, Ni, Pb, Hg and As) in water and sediments of 13 sampling points of Wulungu Lake were analyzed. Geological accumulation index method and potential ecological hazard index method show that Hg has a strong potential ecological risk, which leads to a high potential ecological risk in Wulungu Lake. The water quality of Wulungu Lake is good, but we need to pay attention to the health risk of as. Multivariate statistical analysis shows that Cu, Cd, Zn, Ni and Pb in the water body of Wulungu Lake are affected by the discharge of mining or enterprise wastewater. Hg and Cr may come from the use of fertilizer in farmland. Cr, Cu, Zn, Ni and As in surface sediments are mainly affected by regional geochemical characteristics, while Cd, Pb and Hg are also affected by human activities. The distribution of heavy metals in sediments is different from that in water, which should also be affected by the hydrological conditions of lakes.